Impact Of The Workplace Environment And Employee Performance - Chevy Herli Sumerli A; Harun Samsudin; Aprih Santoso; Arwin Tannuary; Adrian Polim (STIE AMKOP, 2023)
The purpose of this study was to determine how environmental factors and workplace stress affected employee performance at Hotel SantikaGarut. The sample for the study consists of 101 workers of Hotel SantikaGarut. The nonprobability sampling or saturated sampling approach used in this study included a sample of 54 Hotel SantikaGarut employees. When analysing data, descriptive and statistical analysis techniques are also used. and methods for collecting information, such as surveys, interviews, and documentation studies. The results of the study show a strong connection between the work environment at Hotel Santika Garut and employee performance. The work environment at Hotel Santika Garut is the main element influencing employee performance. Say Key: Stress Work, Environment Work, Performance